Glycolytic Bias in mTORC2 Deficient Dendritic Cells Potentiates Antigen-Specific Immunity and Accelerates Graft Rejection. (July 2018) - Watson, Alicia; Dai, Helong; Diaz-Perez, Julio A; Menk, Ashley V; Killeen, Meaghan E; Delgoffe, Greg M; Mathers, Alicia R; Thomson, Angus W
Abstract : Background/Hypothesis: The mechanistic target of rapamycin (mTOR) is known to function in two discrete complexes: mTOR complex 1 (mTORC1) and mTORC2. The function of mTORC1 in dendritic cells (DCs) has been studied extensively using rapamycin (RAPA) as an inhibitor. RAPA inhibition of mTORC1 prevents DC maturation, leading to decreased T effector cell proliferation and increased regulatory T cell (Treg) differentiation. Our group has recently demonstrated that mTORC2 deletion in DCs leads to both an enhanced pro-inflammatory DC phenotype and Th1/Th17 allogeneic T cell polarization and proliferation. However, the underlying mechanism has not been resolved. In addition, the role of mTORC2 in DCs in the context of transplantation has not been defined. We hypothesized that ablation of mTORC2 in DCs would alter metabolic activity, resulting in augmented antigen-specific T cell responses and accelerated graft rejection. Methods: To assess the role of mTORC2 in DCs in transplantation, we used models of non-MHC mismatched skin transplantation in which either the graft donor or recipient was deficient in mTORC2 specifically in conventional CD11c+ DC (TORC2DC-/-). Graft survival was monitored; Banff rejection scoring was performed by a blinded pathologist. T cell infiltration and collagen degradation in the graft were determined by immunohistochemistry. To ascertain whether skin-resident TORC2DC-/- could augment inflammatory responses, we performed a cell-mediated delayed-type hypersensitivity assay. As mTORC2 has been implicated in cytoskeletal dynamics, we measured DC migration into secondary lymphoid tissue. To elucidate the role of mTORC2 in regulating DC metabolism we analyzed glycolytic capacity and mitochondrial respiratory activity of wild-type (WT) DC and TORC2DC-/- using a Seahorse XF Bioanalyzer. Mitochondrial mass and activity were determined via flow cytometric analysis of MitoTracker Green and TMRE uptake, respectively. ATP production was assessed using a luciferase-based luminescence assay. Results/Conclusions: We demonstrate for the first time, that TORC2DC-/- deficiency in either skin graft donors or recipients accelerates immune-mediated rejection. TORC2DC-/- mice also exhibit enhanced T cell and inflammatory monocytic infiltration in the course of delayed-type hypersensitivity responses. These effects are not due to differential migration of TORC2DC-/- to secondary lymphoid tissue. TORC2DC-/- utilize an altered metabolic program, wherein glycolytic function is enhanced as compared to WT DCs. This metabolic phenotype corresponds with increased viability of TORC2DC-/- after stimulation, which may allow these TORC2DC-/- to persist in secondary lymphoid tissue longer than WT DCs. These findings reveal a novel role for mTORC2 in regulating DC immunometabolism, and may provide a basis for therapeutic targeting of DC metabolism to regulate immune responses in transplantation. NIH T32 AI74490.